The Roman Empire Roots of Imperialism - Morley, Neville (Roots of Imperialism, 2010)
A millennium and a half after the end of the period of its unquestioned dominance, Rome remains a significant presence in western culture. This book explores what the empire meant to its subjects.The idea of Rome has long outlived the physical empire that gave it form, and now holds sway over vastly more people and a far greater geographical area than the Romans ever ruled. It continues to shape our understanding of the nature of imperialism, and thus, however subtly, to influence the workings of the world. Unlike most works on Roman history, this book does not offer a simplistic narrative, with military triumph followed by decline and fall. Instead, it analyses the origins and nature of Roman imperialism, its economic, social and cultural impact on the regions it conquered, and its continuing influence in discussions and debates about modern imperialism.